2021
DOI: 10.2106/jbjs.rvw.21.00148
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Component and Liner Selection for the Prevention of Dislocation After Primary Total Hip Arthroplasty

Abstract: Primary total hip arthroplasty (THA) is a reproducible and efficacious procedure for patients with end-stage osteoarthritis; however, dislocation remains the most common cause of revision arthroplasty.Technological advancements in acetabular component design and liner options, in conjunction with a more comprehensive understanding of the spinopelvic factors that influence dislocation, will likely reduce the risk of dislocation and revision over time.The contemporary liner and shell options for primary THA, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…A neutral liner should be used when the surgeon is satisfied with the acetabular position, the hip stability, and in instances where the patient has no increased risk of dislocation. This liner allows the patient to have the greatest range of motion since the implant will sit flush with the acetabular component but does not give the surgeon any added stability [113]. Some surgeons prefer to use a "lipped or high walled liner" to allow for increased stability due to a larger jump distance in a discrete quadrant (Figure 6).…”
Section: Acetabular Liners: Added Stability When Neededmentioning
confidence: 99%
See 1 more Smart Citation
“…A neutral liner should be used when the surgeon is satisfied with the acetabular position, the hip stability, and in instances where the patient has no increased risk of dislocation. This liner allows the patient to have the greatest range of motion since the implant will sit flush with the acetabular component but does not give the surgeon any added stability [113]. Some surgeons prefer to use a "lipped or high walled liner" to allow for increased stability due to a larger jump distance in a discrete quadrant (Figure 6).…”
Section: Acetabular Liners: Added Stability When Neededmentioning
confidence: 99%
“…Surgeons should be aware that these liners are not indicated in situations with implant malposition or hip impingement. The primary indication for these constraint liners is neuromuscular disorders, abductor deficiency or intraoperative multidirectional instability without hip impingement or implant malposition [113]. This increased constraint is commonly used in more difficult hips and has been shown to have higher revision rates from several mechanisms of failure [120].…”
Section: Acetabular Liners: Added Stability When Neededmentioning
confidence: 99%
“…The acetabular liner is a component of the THA prosthesis that is inserted into the acetabular cup. The liner serves as a cushion between the femoral head and acetabular cup 1,2 . In the past, liners made of Cobalt–Chromium alloy were found to release metal ions due to corrosion, as Hothi et al 3 reported.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the most prominent examples of such recent technological innovations in THA include (1) technology-assisted THA that leverages precision of component placement from patient-specific images or robotic-assisted guides, [4][5][6][7][8] and (2) the development of dual mobility acetabular components with multiple points of articulation that provide increased range of motion and the potential for decreased risk of prosthetic dislocation. [9][10][11][12][13] However, focus turned toward the adoption of few major technologies may subtract from the attention that other laudable technological achievements in THA ultimately gain, and it is imperative to objectively assess progress in THA to guide current and future practice.…”
mentioning
confidence: 99%